Death Note. Vol. 13, How to read - Oba, Tsugumi (Viz Media, 2008)
A guide to the manga series "Death Note" provides character profiles, interviews with the author and artist, plotlines, commentary on the design process, trivia, and a series of side stories not published in the original series.